Health Behaviour Change Interventions for the Promotion of Physical Activity in Rheumatoid Arthritis: A Systematic Review. (7th May 2013) - Cramp, Fiona; Berry, John; Gardiner, Matthew; Smith, Felicity; Stephens, Daniel
Abstract Background Rheumatoid arthritis (RA) is a chronic, inflammatory, autoimmune disease with typical onset between the ages of 40 and 50 years. Increasing levels of physical activity (PA) have been shown to decrease inflammation, reduce pain, increase functional ability and improve self‐esteem in people with RA. Health behaviour change (HBC) interventions have recently shown promise in facilitating the promotion of PA within a range of long‐term conditions. There is currently no evidence synthesis relating to HBC interventions to increase PA in the RA population. Objectives The aim of the present study was to determine whether HBC interventions can increase PA in people with RA and identify optimal interventions or promising constituent components of the HBC interventions. Methods A systematic literature search was conducted to identify randomized, controlled trials investigating the effect of HBC interventions on PA level in adults with RA. Four review authors independently assessed the methodological quality of studies and extracted data based upon predefined criteria. Results Following the application of inclusion/exclusion criteria, three studies remained for inclusion. Two studies reported significant short‐term (<9 months) beneficial effects of HBC upon PA (p < 0.05). Individualized interventions were significantly more effective (p < 0.05). Conclusions Due to methodological flaws and a lack of comparison with usual care, it is not possible to conclude whether HBC interventions can increase PA in the RA population. Although it is possible to highlight promising elements of HBC interventions, such as goal setting and feedback on performance, further research on all specific components, including information provision, behaviour contracts and problem solving, is required to establish conclusive clinical guidelines. Copyright © 2013 John Wiley & Sons, Ltd.